Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Investasi Di Kabupaten Kutai Timur Dengan Variabel Kebijakan Pemberian Izin Sebagai Variabel Mediasi - Suhartini, Suhartini; Aji Sofyan Effendi; Diana Lestari (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the effect of economic growth rate, credit distribution, infrastructure expenditure, and regional budget (APBD) on the number of investment permits issued and the total investment value. The analytical method employed is Partial Least Square (PLS) using secondary data processed through statistical software. The findings show that the research model demonstrates strong explanatory power, with R-square values of 0.872 for investment permits and 0.604 for investment value, both categorized as strong. The Q-square results indicate high predictive relevance, while the SRMR test confirms excellent model fit. Multicollinearity analysis shows no serious disturbances, allowing valid interpretation of inter-variable relationships. Direct effect testing reveals that economic growth rate and credit distribution have a significant positive impact on the number of investment permits, whereas infrastructure expenditure shows a significant negative effect. On the other hand, regional budget allocation has a significant positive impact on investment value. Indirect effect analysis confirms that the number of investment permits mediates the influence of economic growth, credit, and infrastructure expenditure on investment value. Overall, the results emphasize that strengthening economic growth and optimizing the regional budget are dominant factors in encouraging investment realization, both in terms of permits and investment value.